Survival Impact of Nephroureterectomy for De Novo Stage IV Nonmetastatic and Metastatic Upper Tract Urothelial Carcinoma - Lin, Wei-Yu; Lin, Meng-Hung; Yang, Yao-Hsu; Chen, Wen-Cheng; Huang, Cih-En; Chen, Miao-Fen; Wu, Chun-Te (Frontiers in Surgery, 2022)
Background: The beneficial role of nephroureterectomy (NU) in stage IV upper tract urothelial carcinoma (UTUC) is unclear. We investigated the impact of chemotherapy (CT) alone compared with CT plus NU in overall survival (OS) among patients with stage IV nonmetastatic UTUC (nmUTUC) and metastatic UTUC (mUTUC). Patients and Methods: A multicenter retrospective cohort study with UTUC patients was conducted from the Chang Gung Cancer Database (2002–2015) and followed up until August 2017. The patients were categorized as CT alone and CT+NU. OS and hazard ratios (HRs) were assessed by Kaplan–Meier method and Cox proportional hazards model, respectively. Results. This study included 308 patients with stage IV UTUC, comprising those with nmUTUC (n = 139) and mUTUC (n = 169); of them, 122 (39.6%) received NU. Specifically, 91 (74.6%) with nmUTUC and 31 (25.4%) with mUTUC received NU. Patients who received CT+NU exhibited higher 3-year OS (16.7% vs 41.0%, p < 0.001), longer median OS duration (20.7 vs 9.0 months, p < 0.001), and lower HR of death (HR, 0.48; 95% confidence interval [CI], 0.36–0.66; p < 0.001) compared with those who received CT alone. Similarly, longer median OS duration (25.0 vs 7.8 months, p < 0.001) and lower HR of death (HR, 0.37; 95% CI, 0.23–0.59; p < 0.001) were found in patients with mUTUC who underwent CT+NU than in those who received CT alone. Conclusion: Compared with CT alone, NU plus CT can provide benefits in 3-year OS to patients with nonmetastatic and metastatic stage IV UTUC.